Advancement of liquefaction assessment in Chinese building codes. (August 2015) - Sun, H; Liu, F; Jiang, M
Abstract: China has suffered extensive liquefaction hazards in destructive earthquakes. The post-earthquake reconnaissance effort in the country largely advances the methodology of liquefaction assessment distinct from other countries. This paper reviews the evolution of the specifications regarding liquefaction assessment in the seismic design building code of mainland China, which first appeared in 1974, came into shape in 1989, and received major amendments in 2001 and 2010 as a result of accumulated knowledge on liquefaction phenomenon. The current version of the code requires a detailed assessment of liquefaction based on in situ test results if liquefaction concern cannot be eliminated by a preliminary assessment based on descriptive information with respect to site characterization. In addition, a liquefaction index is evaluated to recognize liquefaction severity, and to choose the most appropriate engineering measures for liquefaction mitigation at a site being considered.